PERBEDAAN TUMBUH KEMBANG ANAK TODDLER YANG DIASUH ORANG TUA DENGAN YANG DITITIPKAN DITEMPAT PENITIPAN ANAK (TPA) - Fauzi ' Saputra; Oswati ' Hasanah; Febriana ' Sabrian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The aim of this research was to identify the comparison of growth and development between toddler who was cared by parents at name and in child care facilities. This research used comparative study design with cross sectional approach and the respondent was chosen using cluster sampling techinique. Total sample in this study was 100 respondents devided in 2 groups of toodlers. The instruments of this research were scales and used to gauges to measure the weight and height, and DDST II form. Chi square test used for growth aspects and mann whitney test used for development aspects. The result of this study showed that is no differences on toddlers growth between parent’s care group and child care group (p value = 0,595 > α (0,05)) and there is differences in the development aspect between 2 groups (p value = 0,012 < α (0,05)) where the toddlers development was a better in child care fasilities group than parent’s care group. It is recommended to parents or surrogate parents to do more optimal stimulation to their kids especially toddlers to improve their growth and development. Keywords: child care, development, growth, parent’s care, toddler